A double-blind randomised placebo-controlled trial of topical intranasal corticosteroids in 4- to 11-year-old children with persistent bilateral otitis media with effusion in primary care - Williamson, I; Benge, S; Barton, S; Petrou, S; Letley, L; Fasey, N; Abangma, G; Dakin, H; Little, P (2009)
Objectives: To determine the clinical effectiveness and cost-effectiveness of topical mometasone in children with bilateral otitis media with effusion (OME). Design: A double-blind randomised placebo-controlled trial with an intention to treat analysis; the 10.6% of patients lost to follow-up at 1 month were censored in the analysis. Setting: 76 Medical Research Council General Practice Research Framework practices throughout the UK between 2004 and 2007. Participants: A sample of 217 children aged 4-11 years was selected from those presenting to their GP with one or more episodes of otitis media or earrelated problems in the previous 12 months whom the research nurse confirmed had bilateral glue ear using microtympanometry (B B or B C2 types using a modified Jerger classification) at randomisation. Interventions: Mometasone 50 μg in each nostril or placebo spray once daily for 3 months. Main outcome measures: The primary outcome was the proportions of children cleared of OME assessed by tympanometry at 1 month. Secondary outcomes included clearance at 3 months and 9 months; adverse events; OM8-30 scores (a functional health status responsive disease-specific measure); hearing loss; days with otalgia; cost-effectiveness; and health utilities. Results: Of the topical steroid group, 40.6% (39/96) demonstrated tympanometric clearance (C1 or A type) in one or both ears at 1 month, compared with 44.9% (44/98) of the placebo group. The absolute risk reduction at 1 month was -4.3% (95% CI -18.05% to 9.26%); the odds ratio (OR) was 0.84 (95% CI 0.48 to 1.48). Four covariates were pre-specified for inclusion in logistic regression analysis: age as a continuous variable (p = 0.94), season (p = 0.70), atopy (p = 0.61) and clinical severity (p = 0.006). The adjusted OR (AOR) at 1 month for the main outcome was 0.93 (95% CI 0.50 to 1.75). Secondary analysis at 3 months showed 58.1% of the steroid group had resolved and 52.3% of the placebo group, AOR 1.45 (95% CI 0.74 to 2.84). At 9 months 55.6% of the treated group remained clear in at least one ear and 65.3% of the placebo group, AOR 0.82 (95% CI 0.39 to 1.75). Adverse events (although relatively minor) occurred in 7-22% of children and included nasal stinging, epistaxis, dry throat and cough. The OM8-30 scores (p = 0.55) reported hearing difficulty (p = 0.08), and days with otalgia (p = 0.46) were not significantly different between groups at 3 months. The economic evaluation found the active treatment arm to be dominated by placebo, accruing slightly (but not significantly) higher costs and fewer quality-adjusted life-years (QALYs), with a 24.2% probability that topical steroids are a cost-effective use of NHS resources at a ceiling ratio of £20,000 per QALY gained. Conclusions: Use of topical intranasal corticosteroids is very unlikely to be a clinically effective treatment for OME (glue ear) in the primary care setting. Trial registration: Current Controlled Trials ISRCTN38988331. © 2009 Queen's Printer and Controller of HMSO. All rights reserved.